Cerebrospinal fluid enolase in stroke. Issue 7 (July 1984) - Hay, E; Royds, J A; Davies-Jones, G A; Lewtas, N A; Timperley, W R; Taylor, C B
Abstract : This study relates the level of alpha and gamma enolase in cerebrospinal fluid sampled within 4 days of a stroke to the volume of the cerebral infarct measured on the CT image and to the clinical outcome of the patient. Twenty-eight patients were studied, two with transient ischaemic attacks and 26 with completed stroke due to infarction. The cerebrospinal fluid enolase was raised in the two patients with transient ischaemic attacks and 23 with completed stroke. There was a positive correlation between the volume of the infarct and the level of cerebrospinal fluid alpha and gamma enolase. A high cerebrospinal fluid enolase was always associated with a poor prognosis.